A Comprehensive Review of Nursing Strategies for the Management of Eating Disorders in Adolescents: Exploring Perspectives and Best Practices for Holistic Care - Alsharari, Hailah Thani Murayhil; Alsharari, Ahmed Marayef Matlag; Alsharari, Saleh Mohammed Muflih; Alruwaili, Mashael Mohammed Awad; Alazmi, Majed Mahmoud Duliman; Alsharari, Fahad Musul Saud; Alsharari, Abdalhadi Mohammad M; Alsharari, Sami Ali G; Alsharari, Abdulmajeed Masad Mutiq; Aldhabani, Hissah Hamoud Odhayb; Alshammery , Manefah Safag; Alsharar, Shaker Badi Mutlaq; et al. (Journal of Ecohumanism, 2024)
Background: Eating disorders (EDs) are complex mental health conditions that primarily affect adolescents, leading to significant physical, psychological, and social consequences. The management of EDs necessitates a multidisciplinary approach, with nursing strategies playing a crucial role in facilitating recovery and improving patient outcomes. Methods: This review employs a comprehensive analysis of the current literature surrounding nursing strategies for managing eating disorders in adolescents. Databases such as PubMed, Scopus, and CINAHL were searched for qualitative studies that explore the perspectives of patients, families, and healthcare professionals regarding ED treatment. Thematic synthesis was utilized to identify common themes across different stakeholder viewpoints. Results: The findings reveal three primary themes: the struggle for autonomy, the perception of control, and the importance of holistic treatment approaches. Patients expressed a desire for autonomy while simultaneously feeling constrained by their eating disorders. Family members and healthcare professionals emphasized the need for a balanced focus on physical rehabilitation and psychological well-being. The review highlights the significance of individualized care that addresses the unique experiences and challenges faced by adolescents with EDs. Conclusion: Effective nursing strategies for managing eating disorders in adolescents must incorporate a comprehensive understanding of the patient's experience, promote family involvement, and foster collaborative relationships between healthcare providers and patients. The integration of psychological support with nutritional rehabilitation is essential for enhancing treatment adherence and facilitating long-term recovery. Future research should focus on developing tailored interventions that address the diverse needs of adolescents with eating disorders.